Control home automation with voice command using Arduino - Nur Atikah, Muhamad Ayob (2018)
Nowadays, as we already know the technologies used at home have become increasingly rapidly. For example, in the past there has not been any use of electric power. This matter makes their lives unpredictable with the power source. Meanwhile, in the present time. everything has changed and become fully equipped with the technology that enables users to get electricity. An example is that there has now been a creation of the remote control to turn on the switch, television or fan switch simply by pressing the button on the remote control without the need for a user to switch on the main switch. Additionally, the purpose of this project is to be implemented because, to provide a disparity to the technology currently available. Next, diversify the way to control electrical appliances at home. In our lives, everyone must have felt the condition that we did not get good health or in a tiring situation. This should be done quickly and easily. So, we need technology to solve this problem. Thus, in this system it is created to facilitate the user in controlling electrical equipment using only one application. In this system consists of two main components namely component hardware which is using Arduino Uno R3 and for component software using mobile app. Focus this system on how to develop Automated Systems to control home appliances. This system can make users to control switches with their mobile phones. In conclusion, it is hoped that this system can contribute to the user to enhance and facilitate their lives.